Physical and energetic demand of soccer: A brief review. - Dolci, F.; Hart, N. H.; Kilding, A. E.; Chivers, P.; Piggott, B.; Spiteri, T. (Strength and Conditioning Journal, 2020)
Soccer is a complex and exhaustive team-sport requiring a high level of tactical, technical, and physical ability to succeed. During a competitive match, a random combination of explosive and powerful activities, together with technical and tactical gestures, is performed in an intermittent manner over a 90-minute game. This review presents a detailed analysis and up-to-date synthesis of the literature describing activities and energy system contribution during soccer to provide to strength and conditioning coaches a clear understanding of soccer players' physical needs during competition.